SENAM ZUMBA MENINGKATKAN DAYA TAHAN KARDIOVASKULAR DAN KESEHATAN MENTAL PADA SUBJEK DENGAN SKIZOFRENIA DI RSJ PROVINSI BALI KABUPATEN BANGLI - Jayanti, D.M. Ari Dwi; Tirtayasa, Ketut; Sutjana, I.D.P.; Adiputra, N.; Adiatmika, I.P.G; Sri Handari Adiputra, L.M. Indah (Sport and Fitness Journal, 2017)
Cardiovascular endurance is the ability of cardiorespiratorysystem to provide oxygen for muscle, Hence they can do their work or contraction. Mental health is healthy soul condition and free of psychological symptoms. The aim of this research was to know zumba gymnastic to be able to increase cardiovascular endurance and mental health for subject with schizophrenia at RSJ of Bali Province. The methodology of the research used experimental randomized pre and post-test control group design. The samples consisted of 10 persons as controled groups, without being given treatment by researcher but being given daily activity of living and psychopharmaca. 10 persons as treatment groups provided zumba gymnastic, activity daily of living and psychopharmaca. The exercise was performed three times in a week, for six week with duration 45 minutes at RSJ of Bali Province, Bangli District. The result showed that in control groups, Cardiovascular endurance mean of pre-test 34.30±7.60 ml/kg/minute, post-test 34.00±7.57 ml/kg/minute (p>0.05) was analysed by paired samples test and without being increase mean of cardiovascular endurance. Mental health mean of pre-test 9.20±3.16, post-test 7.90±3.45 (p<0.05) was analysed by paired samples test showing increase mean of mental health was 1.3. In treatment groups, cardiovascular endurance mean of pre-test 31.80±3.15 ml/kg/minute, post-test 33.90±4.48 ml/kg/minute (p<0.05) was analysed by paired samples test, showing increase mean of cardiovascular endurance was 2.1 ml/kg/minute. Mental health mean of pre-test 6.50±2.51, post-test 2.50±1.18 (p<0.05) was analysed by wilcoxon test, showing increase mean of mental health was 4.00. it’s concluded that was that zumba gymnastic increaseds cardiovascular endurance and mental health for subject with schizophrenia at RSJ of Bali Province.